Lack of reciprocity, organizational citizenship behaviors and citizenship fatigue: a tale of two theories - Narciso, Cátia Dimas (2018)
Existing findings on the effects of OCB suggest two contradictory views between OCB and citizenship fatigue: the inertial view, that advocates that OCB leads to more OCB, and the dissipative view that advocates that OCB will end up in too much OCB thus leading to citizenship fatigue. Likewise lack of reciprocity has been intrinsically related with these concepts but not yet empirically tested. Hence this study is set to explore these relations taking OCB and lack of reciprocity as predictors of citizenship fatigue. With a sample of 343 workers, findings show divergent relations between two of OCB dimensions (helping behaviour and personal initiative) thus offering support to both inertial and dissipative view of OCB effects on its own permanence across time. Also, lack of reciprocity was found to be a relevant positive predictor of citizenship fatigue. Results suggest the existence of a more complex relation between OCB and citizenship fatigue than usually stated as well as a central construct of "lack of reciprocity" that subsumes many of current variables expressed as social exchange, psychological contract breach or similar.